Arm muscle area is correlated to handgrip strength in postmenopausal women - Ludwig R. Álvarez-Córdova; Reyes Artacho; Peter Chedraui; Cecilia Arteaga-Pazmiño; Melissa Sánchez-Briones; María D. Ruiz-López (Taylor & Francis Group, 2024)
Objective To analyze the correlation between arm muscle area and handgrip strength among postmenopausal community dwelling low-income women in order to provide an easy anthropometric indicator to assess muscle mass quantity and quality.Methods This was a cross-sectional study involving postmenopausal women (n = 171) from three urban-marginal communities of Guayaquil, Ecuador. Corrected arm muscle area was calculated using the Frisancho formula. Dynapenia was defined as HGS < 16 kg. Spearman's correlation coefficient was calculated at a 5% significance level to test the correlation between corrected arm muscle area and handgrip strength.Results Median (interquartile range: IQR) age of the sample was 72.0 years (17.0). The median of corrected arm muscle area was 34.8 cm2 (20.7). The overall prevalence of dynapenia was 57.9% (n = 99). There was a significant decreasing trend with age regarding all anthropometric characteristics and handgrip strength, as well as a higher prevalence of dynapenia with age. For the whole sample, a statistically significant positive correlation was found between corrected arm muscle area and handgrip strength [r = 0.267; p < .001].Conclusion:  There was a significant yet weak positive correlation between corrected arm muscle area and handgrip strength in this postmenopausal sample. There is a need for additional research in this regard.